TOTAL MIKROBA DAN AKSEPTABILITAS DAGING SAPI MARINASI PADA BERBAGAI LAMA PERENDAMAN GULA LONTAR CAIR (Borassus flabellifer) (Total Microbial and Acceptability of Marinated Beef at different Length of Immersion Time with Liquid Palm Sugar (Borassus flabellifer)) - Manasje Manoah Bani; Wendry Setiyadi Putranto; Kusmajadi Suradi (Jurnal Ilmu dan Teknologi Peternakan, 2020)
In East Nusa Tenggara, liquid palm sugar has been long used as a marination material because this process can reduce beef water activity so that it can reduce the number of microbes. The purpose of this study was to determine the characteristics of microbes (bacteria and yeasts) in inhibiting the growth of pathogenic bacteria and acceptability of beef which was marinated using liquid palm sugar. The experiment was conducted experimentally in a laboratory according to a completely randomized design with 5 treatments of immersion time, namely the immersion for 1 day, 3 days, 5 days, 7 days and 10 days and four replications for each treatment. The results of the study showed that the highest increase in the total plate count was observed for the immersion time of 5 days, following the quadratic equation of Y = 92.46 + 64.53X + -493.09X2 (R2= 0.57), the highest increase of lactic acid bacteria in beef was on 5-day immersion time following the quadratic equation of Y = 52.93 + 63.33X + - 477.15X2 (R2=0.79), and the increase in total yeast of beef over 5-day of immersion time followed the regression equation Y= 46.73 + 18.86X (R2= 0.82). The texture and overall acceptance of marinated beef are preferred for the 5-day immersion, while the color, taste, and flavor are not affected by the length of marination time up to 10 days of immersion.